2015
DOI: 10.1002/ep.12239
|View full text |Cite
|
Sign up to set email alerts
|

HF‐free synthesis of MIL‐101(Cr) and its hydrogen adsorption studies

Abstract: The present study focused on the hydrofluoric acid (HF) free synthesis of chromium based metal organic framework, MIL-101(Cr) and its application for hydrogen storage. MIL-101(Cr) has been synthesized hydrothermally using HF, acetic acid, perfluorobenzoic acid, and without acid. The characterization of the synthesized materials were carried out using powder X-ray diffraction, scanning electron microscopy, thermogravimetric analysis, and surface area (BET) by nitrogen adsorption isotherm at 77 K. The results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 35 publications
5
52
0
Order By: Relevance
“…MIL‐101(Cr) was prepared via a modification of the procedure reported by Rallapalli et al In a typical synthesis process, Cr (NO 3 ) 3 ·9H 2 O (4 g, purity≥99.0%), terephthalic acid (1.54 g, purity≥99.0%) and sodium acetate solution (0.05 M, 50 ml) was added to 250 ml capacity Teflon lined stainless steel autoclave, sonicated (10 min), then placed in a preheated oven at 220 °C for 12 hr. After it was cooled down to room temperature, the mixture was transferred into a beaker.…”
Section: Methodsmentioning
confidence: 99%
“…MIL‐101(Cr) was prepared via a modification of the procedure reported by Rallapalli et al In a typical synthesis process, Cr (NO 3 ) 3 ·9H 2 O (4 g, purity≥99.0%), terephthalic acid (1.54 g, purity≥99.0%) and sodium acetate solution (0.05 M, 50 ml) was added to 250 ml capacity Teflon lined stainless steel autoclave, sonicated (10 min), then placed in a preheated oven at 220 °C for 12 hr. After it was cooled down to room temperature, the mixture was transferred into a beaker.…”
Section: Methodsmentioning
confidence: 99%
“…2, the mechanistic role of the co-catalyst is to serve as a nucleophile to ring-open the epoxide once it is activated by coordination to an electrophilic metal center (presumably a metal in the node of the MOF). [31][32][33] Importantly, previous work has shown that, in batch, the yield of PC without co-catalyst is low. 27 However, we hypothesized that the high ratio of MOF catalyst to epoxide in a packed bed ow reactor relative to that in a batch reactor might result in increased reactivity, and that nucleophilic functional groups present at the MOF nodes (e.g., hydroxides, chlorides, uorides, or carboxylates derived from the MOF synthesis) and/or in solution (e.g., water in the solvent) could potentially serve as nucleophiles under these conditions.…”
Section: Development Of Ow Reaction Conditionsmentioning
confidence: 99%
“…Fluoride anions have an affinity to the chromium at the metal center of MOF building units and their interaction assists the stability of the crystal structure 22 . Nevertheless, recent studies [23][24][25][26] have used alternative synthetic methods by replacing fluoride with hydroxide anions using deionized water [23][24][25] . In this work, the self-assembly of MIL-101 (Cr) SBU from its constituent half-SBUs is studied as a prototypical example to highlight the most important stages of nucleation.…”
Section: Introductionmentioning
confidence: 99%